Azine N-oxides as effective controlling groups for Rh-catalysed intermolecular alkyne hydroacylation - Moseley, DF; Kalepu, J; Willis, MC (Royal Society of Chemistry, 2021)
Heterocycle-derived aldehydes are challenging substrates in metal-catalysed hydroacylation chemistry. We show that by using azine N-oxide substituted aldehydes, good reactivity can be achieved, and that they are highly effective substrates for the intermolecular hydroacylation of alkynes. Employing a Rh(I)-catalyst, we achieve a mild and scalable aldehyde C–H activation, that permits the coupling with unactivated terminal alkynes, in good yields and with high regioselectivities (up to >20 : 1 l:b). Both substrates can tolerate a broad variety of functional groups. The reaction can also be applied to diazine aldehydes that contain a free N-lone pair. We demonstrate conversion of the hydroacylation products to the corresponding azine, through a one-pot hydroacylation/deoxygenation sequence. A one-pot hydroacylation/cyclisation, using N-Boc propargylamine, additionally leads to the synthesis of a bidentate pyrrolyl ligand.